Digital-Based Movement Learning on Learning Outcomes and Motivation of High School Students - Ikhsan, Haerul (Edumaspul: Jurnal Pendidikan, 2025)
Physical education at the high school level requires more complex motor skills and a deep understanding of movement techniques. The use of digital technology in learning is one innovation that can improve the quality of physical education. This study aims to determine the effect of digital-based movement learning on the learning outcomes and learning motivation of high school students. This study uses a quantitative approach with a quasi-experimental design using a pretest-posttest control group design. The research sample consisted of 64 grade XI students divided into an experimental group and a control group. The research instruments were a movement skills test and a learning motivation questionnaire. Data analysis was performed using normality tests, homogeneity tests, and independent t-tests. The results showed that digital-based movement learning had a significant effect on the learning outcomes and learning motivation of high school students.